The Influence of Brand Image and Product Quality on the Decision to Buy Suzuki Ertiga Brand MPV Cars in Riau - Ogi Rifansyah; Frini Karina Andini; Achmad Fajri Febrian; Bertliussaza (Department of Business Administration Politeknik Negeri Sriwijaya, 2026)
This study aims to analyze the influence of brand image and product quality on Suzuki Ertiga car purchase decisions. This study uses a quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) version 4 method. Data was collected through a questionnaire on consumers who had bought a Suzuki Ertiga car in Riau. The results of the analysis show that brand image and product quality have a positive and significant effect on purchase decisions. Brand image creates a positive perception in the minds of consumers, while product quality increases consumer confidence in the product. The R-square value of 0.574 indicates that 57.4% of the purchase decision variables can be explained by brand image and product quality. These findings can be the basis for companies to develop marketing strategies based on brand image and product excellence.